134k views
3 votes
Here is the picture it says xxxxxxxxxxxxxxxxxxx

Here is the picture it says xxxxxxxxxxxxxxxxxxx-example-1

2 Answers

1 vote

Answer:

Explanation:

given: 5^3/5^7

= 1/5^(7-3)

= 1/5^4

= 1/625

final answer: 1/625

User Calvillo
by
5.4k points
3 votes

Answer:


5^(-4)

Explanation:

using the rules of exponents


(a^(m) )/(a^(n) ) =
a^((m-n))


a^(-m) =
(1)/(a^(m) )

given


(5^(3) )/(5^(7) )

=
5^((3-7))

=
5^(-4)

=
(1)/(5^(4) ) ← if required with a positive exponent

User Kasra Rahjerdi
by
5.2k points